Stress-Induced Depression Is Alleviated by Aerobic Exercise Through Up-Regulation of 5-Hydroxytryptamine 1A Receptors in Rats - Kim, Tae Woon (Int Neurourol J, 2015)
PURPOSE: Stress is associated with depression, which induces many psychiatric disorders. Serotonin, also known as 5-hydroxy-tryptamine (5-HT), acts as a biochemical messenger and regulator in the brain. It also mediates several important physiological functions. Depression is closely associated with an overactive bladder. In the present study, we investigated the effect of treadmill exercise on stress-induced depression while focusing on the expression of 5-HT 1A (5-H(1A)) receptors in the dorsal raphe. METHODS: Stress was induced by applying a 0.2-mA electric foot shock to rats. Each set of electric foot shocks comprised a 6-second shock duration that was repeated 10 times with a 30-second interval. Three sets of electric foot shocks were applied each day for 7 days. For the confirmation of depressive state, a forced swimming test was performed. To visualize the expression of 5-HT and tryptophan hydroxylase (TPH), immunohistochemistry for 5-HT and TPH in the dorsal raphe was performed. Expression of 5-H(1A) receptors was determined by western blot analysis. RESULTS: A depressive state was induced by stress, and treadmill exercise alleviated the depression symptoms in the stress-induced rats. Expressions of 5-HT, TPH, and HT 1A in the dorsal raphe were reduced by the induction of stress. Treadmill exercise increased 5-HT, TPH, and HT 1A expressions in the stress-induced rats. CONCLUSIONS: Treadmill exercise enhanced 5-HT synthesis through the up-regulation of 5-HT(1A) receptors, and improved the stress-induced depression. In the present study, treadmill exercise improved depression symptoms by enhancing 5-HT(1A) receptor expression. The present results suggest that treadmill exercise might be helpful for the alleviation of overactive bladder and improve sexual function.